An Effective Treatment of Perimenopausal Syndrome by Combining Two Traditional Prescriptions of Chinese Botanical Drugs - Lan, Junjie; Wu, Caiming; Liang, Wen’na; Shen, Jianying; Zhuo, Zewei; Hu, Liu; Ruan, Luwei; Zhang, Pengheng; Ye, Xiangrong; Xu, Leqin; Li, Chengfu; Lin, Shengyuan; et al. (Frontiers in Pharmacology, 2021)
Ethnopharmacological relevance: Two types of traditional Chinese formulas of botanical drugs are prescribed for treating perimenopausal syndrome (PMS), a disorder in middle-aged women during their transition to menopause. One is for treating PMS as kidney deficiency due to senescence and declining reproductive functions, and the other is for treating it as liver qi stagnation in association with stress and anxiety. Despite the time-tested prescriptions, an objective attestation to the effectiveness of the traditional Chinese treatment of PMS is still to be established and the associated molecular mechanism is still to be investigated. Materials and methods: A model for PMS was generated from perimenopausal rats with chronic restraint stress. The effectiveness of traditional Chinese formulas of botanical drugs and a combination of two of the formulas was evaluated based on 1H NMR plasma metabolomic, as well as behavioral and physiological, indicators. To investigate whether the formulas contained ligands that could compensate for the declining level of estrogen, the primary cause of PMS, the ligand-based NMR technique of saturation transfer difference was employed to detect possible interacting molecules to estrogen receptors in the decoction. Results: Each prescription of the classical Chinese formula moderately attenuated the metabolomic state of the disease model. The best treatment strategy however was to combine two traditional Chinese formulas, each for a different etiology, to adjust the metabolomic state of the disease model to that of rats at much younger age. In addition, this attenuation of the metabolomics of the disease model was by neither upregulating the estrogen level nor supplementing an estrogenic compound. Conclusions: Treatment of PMS with a traditional Chinese formula of botanical drugs targeting one of the two causes separately could ameliorate the disorder moderately. However, the best outcome was to treat the two causes simultaneously with a decoction that combined ingredients from two traditional prescriptions. The data also implicated a new paradigm for phytotherapy of PMS as the prescribed decoctions contained no interacting compound to modulate the activity of estrogen receptors, in contrast to the treatment strategy of hormone replacement therapy.